Level of psychological stress among nurses working in the health sector: a field study at the Ben Boulaïd University Hospital Center and the local health sector branch in the city of Bougara (Blida) - benabbad, fethi; Kassmi, Imane (El Omda in Linguistics and Discourse Analysis, 2024)
THE PRESENT STUDY AIMS AT IDENTIFYING THE LEVEL OF PSYCHOLOGICAL STRESS AMONG NURSES WORKING IN THE HEALTH SECTOR. IT ALSO AIMS TO IDENTIFY THE LEVEL OF DIFFERENCES BETWEEN THE PSYCHOLOGICAL PRESSURE LEVELS OF MALE AND FEMALE NURSES. TO ACHIEVE THE OBJECTIVES OF THE STUDY, WE APPLIED A STRESS GAUGE TO A SAMPLE OF 30 NURSES, WE USED THE COMPARATIVE DESCRIPTIVE HYPOTHESIS, BECAUSE OF ITS SUITABILITY AND STUDY OBJECTIVES, AND AFTER THE STATISTICAL PROCESSING OF THE STATISTICAL PROGRAM, WE FOUND THAT THE NURSES WORKING IN THE HEALTH SECTOR HAVE A HIGH LEVEL OF PSYCHOLOGICAL STRESS, AND THAT THERE ARE NO STATISTICALLY SIGNIFICANT DIFFERENCES IN THE LEVEL OF PSYCHOLOGICAL STRESS BETWEEN MALE NURSES AND WOMEN.